2 | ÷ | x | + | 1 | ÷ | ( | x | + | 66 5 | ) | = | 1 | ÷ | 90 |
Multiply both sides of the equation by: | x |
2 | + | 1 | ÷ | ( | x | + | 66 5 | ) | × | x | = | 1 | ÷ | 90 | × | x |
Multiply both sides of the equation by: | ( | x | + | 66 5 | ) |
2 | ( | x | + | 66 5 | ) | + | 1 | x | = | 1 | ÷ | 90 | × | x | ( | x | + | 66 5 | ) |
2 | x | + | 2 | × | 66 5 | + | 1 | x | = | 1 | ÷ | 90 | × | x | ( | x | + | 66 5 | ) |
2 | x | + | 2 | × | 66 5 | + | 1 | x | = | 1 | ÷ | 90 | × | x | x | + | 1 | ÷ | 90 | × | x | × | 66 5 |
2 | x | + | 132 5 | + | 1 | x | = | 1 90 | x | x | + | 11 75 | x |
3 | x | + | 132 5 | = | 1 90 | x | x | + | 11 75 | x |
x1= | - | √139898699 √1750000 |